Rate of benign histology after resection of suspected renal cell carcinoma: multicenter comparison between Korea and the United States - Chang Wook Jeong; Jang Hee Han; Seok Soo Byun; Cheryn Song; Sung-Hoo Hong; Jinsoo Chung; Seong Il Seo; Hong Koo Ha; Eu Chang Hwang; Ill Young Seo; Joseph G. Cheaib; Phillip M. Pierorazio; et al. (BMC Cancer, 2024)
Abstract Background In the United States, the rate of benign histology among resected renal tumors suspected to be malignant is increasing. We evaluated the rates in the Republic of Korea and assessed the racial effect using recent multi-institutional Korean-United States data. Methods We conducted a multi-institutional retrospective study of 11,529 patients (8,812 from The Republic of Korea and 2,717 from the United States) and compared the rates of benign histology between the two countries. To evaluate the racial effect, we divided the patients into Korean, Asian in the US, and Non-Asian in the US. Results The rates of benign histology and small renal masses in Korean patients were significantly lower than that in United States patients (6.3% vs. 14.3%, p < 0.001) and (≤ 4 cm, 7.6% vs. 19.5%, p < 0.001), respectively. Women, incidentaloma, partial nephrectomy, minimally invasive surgery, and recent surgery were associated with a higher rate of benign histology than others. Conclusions In Korea, the rate of benign histology among resected renal tumors was significantly lower than that in the United States. This disparity could be caused by environmental or cultural differences rather than racial differences. Our findings suggest that re-evaluating current context-specific standards of care is necessary to avoid overtreatment.